A case of partial aortic balloon occlusion in an unstable multi-trauma patient. (April 2016) - Hörer, Tal M; Cajander, Per; Jans, Anders; Nilsson, Kristofer F
The usage of aortic balloon occlusion or resuscitative endovascular balloon occlusion of the aorta in trauma management for bleeding control is increasing rapidly as an alternative to thoracotomy and aortic clamping. Little is known about the effects of partial occlusion of the aorta as a bridge to definitive treatment, but one of its advantages may be limited visceral organ ischemia. We describe the first known case of partial aortic balloon occlusion in trauma for reaching a targeted systolic blood pressure, which was used as an adjunctive tool in trauma management and as a bridge to definitive treatment.